Abnormalities of the endocannabinoid system produce piercing nuclear hernias in migrating cerebral neurons - Yury M. Morozov; Pasko Rakic (iScience)
Summary: We are reporting powerful streams of chromatin rupturing the nuclear envelope (NE) and the plasma membrane of migrating cerebral neurons in mouse embryos, which we suggest naming “piercing nuclear hernia” (PNH). About 40% of migrating neurons in cannabinoid type 1 receptor knock-out (CB1R−/−) mouse embryos and in wildtype embryos exposed to CB1R agonists show NE rupture and/or PNH. This indicates that deviations from optimal functioning of the endocannabinoid system in under- or over-activity may trigger analogous mechanisms increasing intranuclear pressure and chromatin herniation. The cells from CB1R−/− embryos showed pronounced ultrastructural disorders, such as high volume of herniated chromatin, mitochondrial fission, and negative correlation of the mitochondrial length with the volume of herniated chromatin. Catastrophic rupture of the nuclear and plasma membranes may provoke accidental cell death. At the same time, a fraction of neurons with PNH showed generally normal ultrastructure, which could indicate a mechanism of cell body repair.